STUDENTS’ READING HABITS AT THE ENGLISH EDUCATION DEPARTMENT OF UNIVERSITAS NEGERI MANADO - Usnatun Hasanah Sarono; Nihta V. F. Liando; Tirza A. Kumayas (Program Studi Pendidikan Bahasa Inggris, 2023)
This research aims to find out the reading habits of the students of class 2018 at English Education study program. This research was conducted at English Education Department, Faculty of Languages and arts Universitas Negeri Manado. Descriptive quantitative survey was the method used in this research and the instrument to collecting data by using a questionnaire. That was distributed to 25 students. The result of this research showed that the respon of students’ reading habits based on their experiences to the statements was mostly positive. And researcher concluded that the students of class 2018 at English Education Study Program, English Education Department of Universitas Negeri Manado who were the samples in this study like to read, feel happy, and are also excited when reading. They also love to read for fun and to get information. Hopefully, this research can present information as reference material for the next researchers and English teachers in providing assistance, motivation to maintain good reading habits, improve teaching techniques, in order to increase and improve their English reading skills.